OC-035 Rates of catheter-related bloodstream infection and risk of catheter-related venous thrombosis in patients referred for home parenteral nutrition. (28th May 2012) - Bouri, S; Major, G A D; Hanson, C; Small, M; Gabe, S M
Abstract : Introduction: Parenteral nutrition (PN) via a central venous catheter (CVC) is associated with risk of thrombosis and catheter-related bloodstream infection (CRBSI). Factors believed to reduce the risk of infection include using a tunnelled CVC or peripherally inserted central catheter (PICC), and using a single lumen CVC where possible. A CVC tip above the mid-section of the superior vena cava increases thrombosis risk. 1 Strict aseptic technique is required to prevent CRBSI. Methods: Between 1st January and 31st December 2011 patients transferred to the St Mark's Intestinal Failure Unit with a CVC in situ for PN were assessed. We recorded CVC type, number of lumens, and CVC tip position (see Abstract OC-035 figure 1 : dashed lines (mid & proximal superior vena cava (SVC), brachiocephalic, subclavian & internal jugular veins) & solid lines (distal third SCV, proximal & distal right atrium). CVC tip position in the dashed region is associated with a higher thrombosis risk (Cadman et al ). 1 Blood cultures were taken from all lumens of the CVC. CVCs with bacteraemia were treated with antibiotics. If a CVC was felt to be unusable it was removed. Reasons included tip position, multiple lumens, unsuitable for long-term use (not PICC or tunnelled), or for use by patient (PICC), CVC-related sepsis, CRBSI at risk of seeding ( S aureus or fungus), and >1 CVC in situ. Results: 60 patients with 65s CVC from other centres were transferred. Some patients were admitted more than once. 24 were female and 36 were male, from 41 English Hospitals & two from Kuwait. 21 CVCs were tunnelled, 22 untunnelled, 21 were PICCs and one was a midline. Results are summarised in Abstract OC-035 table 1 . 32(48%) CVCs had a tip that was too high, increasing thrombosis risk. 32% (21/65) of blood cultures were positive. 12 (18%) CVCs were retained and used. 13 (20%) were removed because of discontinuation of PN. 38 (58%) of CVCs were replaced. Conclusion: This data demonstrates that on transfer patients CVCs are often infected, have a tip that is too high and multi-lumen CVCs are placed inappropriately. Reasons may include lack of attention to aseptic technique, lack of awareness of the thrombosis risk from a high CVC tip, and lack of availability of single lumen tunnelled CVCs as stock. Competing interests: None declared. Reference: 1. Cadman A, Lawrance JAL, Fitzsimmons L, et al. To clot or not to clot? That is the question in central venous catheters. Clin Radiol 2004;59 :349–55.